Effect of standardized ileal digestible lysine on growth and subsequent performance of weanling pigs - Nemechek, Jeremiah E (Transl Anim Sci, 2018)
A total of 320 weanling pigs (all barrows, initially 5.71 kg BW; Line 1050, PIC Hendersonville, TN) were used to determine whether the Lys level fed during one phase of the nursery influences the response to Lys during subsequent phases. Our hypothesis was that feeding decreasing dietary Lys concentration in early phases, but feeding adequate concentrations in later phases might result in similar pig growth as those fed a more conventional approach with step-wise decreases in dietary Lys as pigs become heavier. Eight dietary regimens were used in a split-plot design. There were three dietary phases, and within phase, a high or low standardized ileal digestible (SID) Lys diet was fed. Pigs were fed either 1.35% or 1.55% SID Lys during phase 1 (days 0 to 7), 1.15% or 1.35% SID Lys in phase 2 (days 7 to 21), and 1.05 or 1.25% SID Lys during phase 3 (days 21 to 35). The low dietary Lys concentrations were achieved by reducing both crystalline Lys and intact protein sources from the high Lys diets. From days 0 to 7, feeding high SID Lys improved (P < 0.01) G:F, but no evidence for differences in ADG or ADFI were observed. Similarly, from days 7 to 21, there were no evidence for differences in ADG or ADFI among pigs fed the two Lys levels, but those fed high SID Lys had improved (P < 0.03) G:F. From days 21 to 35, pigs fed the high Lys diet had increased (P < 0.01) ADG and G:F compared with those fed low SID Lys, but there were no effects on ADFI. For the overall trial (days 0 to 35), there were no dietary interactions among phases, indicating that the Lys level fed in each phase did not influence the response to Lys in subsequent phases. Thus, pigs fed the high Lys level during phase 3, regardless of previous Lys levels in phases 1 and 2, had greater (P < 0.05) overall ADG and G:F compared with other treatment groups. In conclusion, relatively low dietary Lys concentrations can be fed in the early nursery phases (approximately 6 to 12 kg) without any negative impact on overall growth performance provided that adequate Lys levels are fed thereafter (12 to 20 kg).